Відповідь:
3)
Пояснення:
√(4-√(1-х))>√(2-х)
ОДЗ: 2-х>=0 & 16>=1-х>=0
х=<2 & -15=<х=<1
хє[-15;1]
4-√(1-х)>2-х
х+2>√(1-х)
(х+2)^2>1-х
х^2+4х+4>1-х
х^2+5х+3>0
х=(-5±√(25-12))/2
х=(-5±√13)/2
х1=(-5+√13)/2, х=(-5-√13)/2
_-15__+___(-5-√13)/2-(-5+√13)/2_+__1_+___
хє( -5-√13)/2; 1]
Відповідь:
3)
Пояснення:
√(4-√(1-х))>√(2-х)
ОДЗ: 2-х>=0 & 16>=1-х>=0
х=<2 & -15=<х=<1
хє[-15;1]
4-√(1-х)>2-х
х+2>√(1-х)
(х+2)^2>1-х
х^2+4х+4>1-х
х^2+5х+3>0
х=(-5±√(25-12))/2
х=(-5±√13)/2
х1=(-5+√13)/2, х=(-5-√13)/2
_-15__+___(-5-√13)/2-(-5+√13)/2_+__1_+___
хє( -5-√13)/2; 1]